Decision making of individuals with heroin addiction receiving opioid maintenance treatment compared to early abstinent users. (1st December 2019) - Kriegler, Julia; Wegener, Sophia; Richter, Francois; Scherbaum, Norbert; Brand, Matthias; Wegmann, Elisa
Highlights: Emphasizing the relevance of opioid maintenance treatment (OMT) in heroin addiction. Comparison of two different groups of patients with heroin addiction. Long-term OMT associated with functional decision making. OMT associated with lower craving reactions. Relevance of OMT for relapse prevention. Abstract: Background and aims: Individuals with heroin addiction are prone to dysfunctional decision-making. They frequently choose the short-term rewarding option of drug intake despite experiencing long-term negative consequences. Opioid maintenance treatment (OMT) is the most common treatment of heroin addiction. Methods: In this study, 38 individuals in an early stage of abstinence from heroin addiction (ESA-HA individuals) at the end of inpatient detoxification treatment and 41 individuals in long-term OMT were examined. Decision-making was assessed by (I) a modified version of the Iowa Gambling Task (IGT) with drug-related stimuli focusing on decision-making under ambiguity and (II) the Game of Dice Task (GDT) assessing decision-making under objective risk. Results: OMT-individuals showed significantly better performance in the IGT than the ESA-HA-individuals. They also showed significantly less craving under exposure of drug-related pictures. In the GDT, OMT-individuals showed significantly less risky decision-making than ESA-HA-individuals. Conclusion: The results suggest that patients receiving OMT show better functional decision-making and lower craving reactions. It could be assumed that the effectiveness of OMT in preventing relapse is linked to better decision-making and lower craving among these patients.